Integration of Religion and Science from Abdus Salam's Perspective - Nurhidayati Hasanah; Eva Dewi; Heni Julaika Putri (Bulletin of Indonesian Islamic Studies, 2025)
This article examines Abdus Salam's thoughts on the integration of religion and science in the context of the development of modern Islamic science. This study aims to describe the philosophical foundations, integration models, and the relevance of Salam's ideas in responding to the challenges of contemporary science. The study uses qualitative methods through literature review using documentation techniques on Salam's primary works, scientific books, and recent journal articles. Data analysis was conducted using content analysis to identify key concepts and link them to Islamic scientific discourse. The results show that Salam built the integration of religion and science based on the principle of monotheism, which views the order of nature as a manifestation of God's will. His integration model encompasses epistemological, axiological, and educational dimensions, emphasizing that scientific activity must have a moral and welfare orientation. These findings contribute to the strengthening of the Islamic scientific paradigm that harmoniously combines revelation and empiricism. This study concludes that Salam's thoughts remain relevant in addressing contemporary issues such as artificial intelligence, biotechnology, and the revitalization of science in the Muslim world, and offers a conceptual framework for the development of character-based Islamic education.